HER2/neu testing for anti-HER2-based therapies in patients with unresectable and/or metastatic gastric cancer. Issue 8 (8th May 2012) - Gómez-Martin, Carlos; Garralda, Elena; Echarri, M José; Ballesteros, Anabel; Arcediano, Alberto; Rodríguez-Peralto, José Luis; Hidalgo, Manuel; López-Ríos, Fernando
Abstract : Aim: To study the HER2 gene amplification or overexpression in patients with advanced gastric cancer (GC) and their association with patient characteristics and patient survival. Patients and methods: Tumour tissue samples from 148 patients with advanced GC were studied for HER2 by immunohistochemistry (IHC), fluorescence in situ hybridisation (FISH) and dual colour silver enhanced in situ hybridisation (dc-SISH) methods. Clinicopathological data from all patients were collected. Progression free survival and overall survival were also analysed. Results: Mean age was 67 (33–83) years; 75% were male subjects, and 51% had intestinal histological type. HER2+ rates were 10.1% (15/148) by IHC, 18.2% (27/148) by FISH+ or 21.6% (32/148) by dc-SISH+. There were significant differences in HER2+ rates according to histological type when FISH (intestinal, 23%; no intestinal, 4%; p<0.0001) or dc-SISH (intestinal, 26%; no intestinal, 6%; p<0.0001) amplification techniques were used. Median overall survival was significantly longer in HER2+ patients despite the determination technique used: IHC (21.4 vs 9.8 months, HR 0.42; p=0.005); FISH (19.6 vs 9.7 months, HR 0.49; p=0.007) or dc-SISH (19.6 vs 9.7 months, HR 0.53; p=0.009). Factors associated with favourable survival in the multivariate analysis were intestinal type and Her2+ determination by IHC, FISH or dc-SISH. Conclusion: HER2 gene amplification is significantly associated with patient survival. HER2 gene amplification approaches might be an optimal HER2/ neu testing strategy for the selection of HER2+ GC patients who are candidates to be treated with anti-HER2 therapies.